Pelanggaran Hak Asasi Manusia Terhadap Tradisi Kawin Culik Suku Sasak - Zulfa, Lale Indana; Syihabuddin, Syihabuddin (Jurnal Ilmiah Wahana Pendidikan, 2024)
The tradition of a kidnap marriage is a marriage practice where a man kidnaps a woman. Today, the old kidnap marriage procession is changing. The misuse of the kidnap marriage procession causes human rights violations. The purpose of this research is to see the form of human rights violations and the form of the kidnap marriage procession. This research is qualitative research with a descriptive method, with data in the form of YouTube videos on the Lombok Culture and Tourism and Mandalika accounts. The data analysis techniques used are data reduction, data presentation, and conclusions. Based on the results of the research, human rights violations were found in the form of lack of freedom of expression for the female party, and male domination in the marriage procession. Then, the abducted marriage procession detected in this study is the mbait and mesejati or selabar procession. Some factors influence the occurrence of kidnap marriages; 1). culture, 2). economy, 3). parental conflict, 4). arranged marriage.